Pengembangan Sistem Seleksi dan Monitoring Atlet Shorinji Kempo Kota Malang berbasis Web - Dwi Tyas Fitriya Ningsih; Edy Santoso; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Shorinji kempo is a martial art originating from Japan and began to develop in Indonesia since 1966. Now, martial arts are not only used for self-defense, but there have also been regional, national and international championships. Prior to participating in the championship, prospective athletes will be selected to choose the best in terms of physical and technical aspects. Then there will be coaching athletes for several months. The selection and coaching of sports athletes is handed over directly to the management of the sports branch. So that the Malang KONI did not know directly the results of the selection. Assessment during selection is also still done manually and conventionally, namely on a sheet of paper. In addition, the athlete's progress every day is not recorded regularly so that it cannot be known whether the athlete has decreased or increased either physically or technically. Based on these problems, the researchers proposed a system for athlete selection, and related parties could immediately see the results so that there was no cheating. At the time of coaching athletes there is monitoring of athlete performance during daily training. The system development method uses the waterfall development method. From the implementation carried out, it produces the main features of athlete selection, athlete development graphs and recommendations for physical exercise. The system is built with the MVC architecture using the Codeigniter framework. System testing using white box testing and black box testing methods.